2006
DOI: 10.1007/s10664-006-9020-6
|View full text |Cite
|
Sign up to set email alerts
|

Experiences from introducing UML-based development in a large safety-critical project

Abstract: UML and UML-based development methods have become de facto standards in industry, and there are many claims for the positive effects of modelling object-oriented systems using methods based on UML. However, there is no reported empirical evaluation of UML-based development in large, industrial projects. This paper reports a case study in ABB, a global company with 120,000 employees, conducted to identify immediate benefits as well as difficulties and their causes when introducing UML-based development in large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 17 publications
0
43
0
Order By: Relevance
“…The first study [4], investigated the effects of adopting UML-based development on the company's development process. The results showed that the UML-based method led to improved traceability of requirements to code, improved communication within the development teams (and to some extent in the reviews), improved design of the code, quicker development of test cases and better coverage of these, and a product that was better documented than were previous products.…”
Section: Earlier Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The first study [4], investigated the effects of adopting UML-based development on the company's development process. The results showed that the UML-based method led to improved traceability of requirements to code, improved communication within the development teams (and to some extent in the reviews), improved design of the code, quicker development of test cases and better coverage of these, and a product that was better documented than were previous products.…”
Section: Earlier Studiesmentioning
confidence: 99%
“…Several benefits have previously been reported related to improved documentation, design and testing in the company. However, challenges have also been noted, particularly those that are caused by the company's large base of legacy code [3,4,27]. The study reported in this paper focuses on the use case modelling part of the UML-based development.…”
Section: Introductionmentioning
confidence: 99%
“…but since larger development projects typically are broken down into smaller parts, and individual parts are often modelled by different teams (Anda et al, 2004), the task of the experiment may be representative for small tasks in industrial development projects. The class diagrams created by the subjects of the experiments contained between four and thirteen classes.…”
Section: The Role Of Use Cases In the Construction Of Class Diagramsmentioning
confidence: 99%
“…This task may influence the results. In particular, the results may be different on a larger system, and if development is based on existing systems (Anda et al, 2004).…”
Section: Experimental Materialsmentioning
confidence: 99%
“…Use cases have gradually become a widely accepted requirement specification technique both in research domain [2,10,13,32,33,74,103,151] as well as, to some extent, in industrial practice [8,9,39,59,109]. Nevertheless, their inherent utilization of natural language and a behavior of requirement documentation in a semi-conventional way, mean that they are affected by issues such as ambiguity, redundancy, inconsistency, and incompleteness [2,32,146].…”
Section: Introductionmentioning
confidence: 99%